TauhÃ®d dan Sikap Tawakkal; dari Passiva Menuju Activa - Thohir, Umar Faruq (Humanistika : Jurnal Keislaman, 2015)
Resignation (tawakkal) means surrendering all affairs only to God and believe everything that happens has been appointed since the time of Azali. However. attitude of resignation can not simply be interpreted as act of submission to Gods dealings with businesses annulled. In this article, the author tries to explore the attitude of resignation that is not solely based on a passive stance (not doing anything) into the meaning of resignation is active through the study were taken from the point of view of some scholars. positive resignation (active) in this article does not mean not recognize the omnipotence of God. Positive resignation still acknowledge the intervention of God in all his success, but only make a positive resignation attitude surrendered (resignation) as an entity of its business. To know about the concept of active resignation in this article, the resignation was discussed in section Tawhid and resignation; asignification, Depth resignation, barrier resignation, and Active resignation; Applicable Tauhid expression, which later would give a conclusion after trying, one must surrender to God about the outcome, because "results" are Lord region.